O06.6 Reduction in adherence to antiretroviral therapy during postpartum: findings from a prospective cohort study. (14th July 2019) - Ajayi, Anthony; Adeniyi, Oladele
Abstract : Background: The WHO recommended breastfeeding as the best feeding option for women with HIV in sub-Saharan Africa. Adherence to anteretroviral therapy is important for breastfeeding mothers to prevent vertical transmission of HIV. There is evidence that pregnancy tends to drive adhrence of antiretroviral therapy among women living with HIV, however it is unclear whether they main the level of adherence at pregnancy during the postpartum period.This study assesses the rate of drop-off in adherence in the post-partum period from the prospective cohort study of mother-infant pairs in Eastern Cape, South Africa. Methods: We conducted a follow up study on 485 mothers with HIV at 18 months post delivery to elucidate on their adherence to ART during their postpartum period. We obtained relevant items on demographic, lifestyle and self-reported adherence to ART. Adherence was measured using 7-items questions to probe adherence to ART since birth of their child to the previous night of the survey. Logistic regression (model) analysis was fitted to determine the predictors of good adherence in the cohort. Results: The mean age of the participants was 32.91 years (Standard Deviation 5.74). About 64% of the women reported complete adherence to ART representing a 5% percentage drop-off in adherence compared to the rate recorded during pregnancy. In the adjusted model, alcohol use in the last 12 months [AOR:2.36; CI:1.57–3.55], younger age [AOR:3.32, CI:1.45–7.63], cohabiting marital status [AOR:2.71, CI:1.10–6.72], not knowing partners' status [AOR:2.11, CI: 1.28–3.48], unemployed [AOR:1.70; CI:1.09–2.68] were associated with a higher likelihood of non-adherence to ART. Conclusion: Drop-off in the postpartum adherence are linked to lifestyle behaviours in the study setting. Targeted screening of these lifestyle behaviours among reproductive age women for intervention would be crucial to prevention of breastfeeding and parter transmission of HIV. Disclosure: No significant relationships.